(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sujarta P, Mailissa MG, Keiluhu HJ, Hadisusanto S, Yuliana S. 2022. Community distribution and utilization of gastropods in the Coastal Area of Liki Island, Sarmi District, Papua, Indonesia. Biodiversitas 23: 5001-5011. Gastropods and snails are mollusk phylum animals with diverse species that inhabit and spread in various marine ecosystems. The main objective of this study was to determine the structure of gastropod communities and their utilization in the coastal area of Liki Island, Sarmi District, Papua, Indonesia. Samples of gastropods were collected through descriptive-quantitative surveys using the line-transects technique. In addition, information on the utilization of gastropods was collected from surveys with semi-structural interviews with selected respondents from Liki Island, the outermost island in East Indonesia, with a total area of 1318.54 ha. The result showed a total of 1812 living specimens from 63 species of gastropods from 23 families, collected from six sampling stations, with 182-603 specimens on average. There were five species of gastropods encountered in all sampling stations, namely Conus litteratus (family of Conidae), Monetaria moneta, Monetaria annulus (Cypraeidae), Oxymeris crenulata (Terebridae), and Polinices flemingianus (Naticidae). The highest Importance Value Index (IVI) belonged to Nerita albicilla (Neritidae) from Station 1 (IVI 58.45). In contrast, the lowest belonged to the species of Nassarius limnaeiformis (Nassariidae), Oliva caerulea, and Oliva oliva (Olividae) from Station 4 (each IVI 2.56), with the moderate value of Shannon-Wiener Diversity Index and low value of Dominance Index. People in the coastal area of Liki Island use 12 species of gastropod as wall ornaments and consume 12 species of gastropod, as well. In general, the people of Liki Island use gastropods wisely based on the socio-cultural characteristics of the local community.